Language Production in a Parkinson's Disease Patient in Banjarnegara: A Psycholinguistic Analysis - Nurharyani, Octaria Putri; Nugroho, Bivit Anggoro Prasetyo; Marahayu, Nila Mega (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
Parkinson's Disease (PD) is a condition caused by damage to the nervous system, which impacts speech functions and is marked by slow movement and speech (bradykinesia). This condition relates to the brain's ability to process speech functions and linguistic information. Parkinson's affects both motor and cognitive abilities, which are integral to speech production and linguistic processing. The research was conducted in Banjarnegara on a 70-year-old patient suffering from Parkinson's Disease. This study employs a qualitative descriptive method, followed by field observations and interviews using audiovisual recording and note-taking techniques. The aim is to analyze the language production produced by a Parkinson's patient as an initial step to identify what language disorders appear. So it is hoped that the results of this identification can be used to follow up on what stage of speech therapy should be given. The data is in the form of language production, consisting of speech in the form of words and sentences. The results of the study found that a Parkinson's patient experienced a decrease in cognitive abilities, which was indicated by difficulty in producing speech when answering questions. Patients try to remember by repeating the words